ANALISIS FAKTOR-FAKTOR FUNDAMENTAL YANG MEMPENGARUHI PENDAPATAN NELAYAN DI GAMPONG UJONG BLANG KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE - Muhammad Rizka; Devi Andriyani (Jurnal Ekonomi Pertanian Unimal, 2020)
This study aims to determine the effect of education, age, experience and number of family members on fishermen income in Ujong Blang, Banda Sakti Sub-district, Lhoksemawe City. This study uses primary data obtained by distributing questionnaires to all respondents. The sample in this study is 96 respondents derived by using the Slovin formula. The data analysis method used is a multiple linear regression. The results partially showed that education and age have a positive and significant effect on income, but the experience and number of family members do not have a positive and significant effect on the income of fishermen in Ujong Blang, Banda Sakti Sub-district. Simultaneously, education, age, experience, and the number of family members have a positive and significant effect on the income of fishermen in Ujong Blang, Banda Sakti Sub-district, Lhoksemawe City.